The Role of Factors of Social Responsibility in Organizational Environmental Sustainability / A Descriptive and Analytical Study of The Opinions of a Sample of Employees at Accounting Firms in Iraq - Kifah Sami Hussein (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research seeks to diagnose the role of social responsibility in environmental sustainability at Accounting firms in Iraq. The research concluded that social responsibility has a significant impact on achieving environmental sustainability. This study examines the close relationship between Corporate Social Responsibility (CSR) and Sustainable Development (SD), where social responsibility plays a crucial role in promoting the economic, social, and environmental dimensions of sustainable development. The findings indicate that integrating CSR practices with sustainable development strategies contributes to achieving a balance between the interests of companies, society, and the environment, and enhances the long-term sustainability of development. The study also addresses the impact of government policies and stakeholder expectations on shaping the sustainable performance of companies.